1994
DOI: 10.1084/jem.179.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dendritic cell recruitment is a hallmark of the acute inflammatory response at mucosal surfaces.

Abstract: SummaryImmunohistochemical analysis of challenge sites such as skin and the peritoneal cavity has identified neutrophils as virtually the sole cellular participants in acute bacterial inflammation, peak influx occurring 24-48 h in advance of mononuclear cell populations associated with adaptive immunity This study challenges the general applicability of this paradigm. We demonstrate here that the earliest detectable cellular response after inhalation ofMoraxdla catarrhalis organisms is the recruitment of putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(256 citation statements)
references
References 14 publications
9
245
0
2
Order By: Relevance
“…injection of an antigen load, at which point they develop antigen-presenting-cell activities and migrate to regional lymph nodes over several days after contact with the antigen (16,17). However, these studies did not assess the involvement of remote lymphoid organs such as the spleen in the immune response.…”
Section: Localization Of the Immune Responsementioning
confidence: 99%
“…injection of an antigen load, at which point they develop antigen-presenting-cell activities and migrate to regional lymph nodes over several days after contact with the antigen (16,17). However, these studies did not assess the involvement of remote lymphoid organs such as the spleen in the immune response.…”
Section: Localization Of the Immune Responsementioning
confidence: 99%
“…In contrast to parenterally administered allergens, orally applicated allergens underlie the activity of salivary enzymes, proteases and the low pH, which as the first line mechanisms of defense inactivate most of the relevant epitopes of the allergens before they reach the APC of the mucosal tissue (66). Regarding the mucosal surfaces of the gastrointestinal tract the primary APC type at the interface to the environment are DC which are regarded as the key factors in controlling T-cell responses in the gut wall (Table 1) (67)(68)(69)(70).…”
Section: Antigen Presenting Cells Of the Gastrointestinal Mucosamentioning
confidence: 99%
“…We have shown that airway RTDC become activated and up-regulate their capacity to capture and process inhaled allergen prior to the onset of Th2-mediated airways inflammation in mice, suggesting that RTDC play an important early role in the activation and recruitment of Th2 cells to the airways (von Garnier et al, 2007). In addition to the airway epithelium, RTDC subsets are also present in the submucosa and lung parenchyma although subset distribution and turnover rates differ at these sites (Holt et al, 1994;von Garnier et al, 2005). We and others have shown that RTDC are capable of capturing inhaled allergens and rapidly transporting these to DLN for presentation to T cells and that the rate of this transport can be modified by microbial products (Vermaelen et al, 2001(Vermaelen et al, , 2003Wikstrom et al, 2006).…”
Section: Distribution and Function Of Respiratory Tract Dendritic Cellsmentioning
confidence: 98%
“…This DC subset has a high migratory capacity for trafficking antigen to the draining lymph nodes (Lambrecht, 2001;Vermaelen et al, 2001;von Garnier et al, 2007). CD11c+MHCIIhi DC in the respiratory mucosa are known to exhibit a high rate of turnover (approximate half-life of 12 h) as antigen-bearing DC continuously migrate to the DLN and are replaced by de novo DC from the bone marrow (Holt et al, 1994;Lambrecht et al, 1998;von Garnier et al, 2005). Although outside the scope of this review, DC migration into and from the airways is modulated by the expression of chemokine receptors (Stumbles et al, 2001;Jakubzick et al, 2006) and can be modified by microbial exposure (McWilliam et al, 1994(McWilliam et al, , 1996Stumbles et al, 2001).…”
Section: Distribution and Function Of Respiratory Tract Dendritic Cellsmentioning
confidence: 99%